Promosi Marketing Pada Butik Cheryl Collection - Cherilya Alfara Natasya; Puji Isyanto; Dini Yani (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
Fashion is an important need for all people. Marketing strategy is a fundamental tool that is designed or planned to achieve the goals of a company by developing a sustainable competitive advantage through the market entered and the program used to serve its target market. The current fashion trend is very interesting to follow and develop according to current needs to attract consumer interest and purchasing power.